COVID-19 infection control education for medical students undergoing clinical clerkship: a mixed-method approach - Hajime Kasai; Go Saito; Shoichi Ito; Ayaka Kuriyama; Chiaki Kawame; Kiyoshi Shikino; Kenichiro Takeda; Misuzu Yahaba; Toshibumi Taniguchi; Hidetoshi Igari; Seiichiro Sakao; Takuji Suzuki (BMC Medical Education, 2022)
Abstract Background Coronavirus disease (COVID-19) has induced an urgent need to train medical students not only in infection prevention control but also in the treatment of infectious diseases, including COVID-19. This study evaluates the impact of simulated clinical practice with peer role-plays and a lecture on clinical education for COVID-19. Methods The sample for the study included 82 fourth- and fifth-year medical students undergoing clinical clerkship in respiratory medicine. They answered questionnaires and participated in semi-structured focus group interviews (FGIs) regarding the advantages of simulated clinical practice with peer role-plays and lectures on clinical education for COVID-19. Results A total of 75 students participated in the COVID-19 education program between January and November 2021. The responses to the questionnaire revealed that the satisfaction level of students with COVID-19 education was high. No significant change was found among students concerning fear of COVID-19 before and after the program. The degree of burden of handling information on COVID-19 reduced significantly, while the degree with respect to the use of personal protective equipment (PPE), including appropriate wearing and removing of PPE, and care of patients with confirmed COVID-19 while taking steps to prevent infection, exhibited a decreasing trend. Nine FGIs were conducted (n = 74). The advantages of simulated clinical practice were segregated into five categories (infection prevention control, educational methods, burden on healthcare providers, self-reflection, and fear of COVID-19); and that of the lecture were segregated into four categories (information literacy, knowledge of COVID-19, educational methods, and self-reflection). Conclusions Simulated clinical practice with peer role-plays and the lecture pertaining to COVID-19 can prove to be efficient and safe methods for learning about COVID-19 infection and prevention control for medical students. They can reduce the burden of COVID-19 patients’ care. Moreover, they can also provide an opportunity for self-reflection, realize the burden of medical care, and acquire relevant information.